2019
DOI: 10.1002/jib.563
|View full text |Cite
|
Sign up to set email alerts
|

West African sorghum beer fermented with Lactobacillus delbrueckii and Saccharomyces cerevisiae: shelf-life and consumer acceptance

Abstract: The fermentation profiles, shelf‐life and consumer acceptance of traditional West African sour sorghum beer (pito) fermented with pure commercial starter cultures of lactic acid bacteria (L. delbrueckii) and yeast (Saccharomyces cerevisiae) were evaluated. The beers from this ‘pure culture’ approach were compared with the spontaneous fermentation of pito wort. Lactic acid formation, pH change and extract utilisation were monitored during fermentation. Lactic acid content was used as a measure of sourness to es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
(27 reference statements)
1
3
0
Order By: Relevance
“…The inclusion of extracts or whole prekese and HS (boiled in wort) could lead to a drop in the pH of wort due to the overwhelming phytochemicals present, hence it should be adjusted with buffers, such as calcium carbonate and calcium sulfate/calcium chloride, before pitching. The pH of the final pito documented by [164] is similar to the values reported earlier. A pocket-sized handheld pH meter is the ultimate easier method that local brewers could adopt in measuring the pH of the mash, wort, and final beer.…”
Section: Phsupporting
confidence: 88%
See 2 more Smart Citations
“…The inclusion of extracts or whole prekese and HS (boiled in wort) could lead to a drop in the pH of wort due to the overwhelming phytochemicals present, hence it should be adjusted with buffers, such as calcium carbonate and calcium sulfate/calcium chloride, before pitching. The pH of the final pito documented by [164] is similar to the values reported earlier. A pocket-sized handheld pH meter is the ultimate easier method that local brewers could adopt in measuring the pH of the mash, wort, and final beer.…”
Section: Phsupporting
confidence: 88%
“…Sensory evaluation of pito brewed with a pure yeast culture and dembila revealed that the panellists found no difference in their overall liking between the two products; however, the pure culture enhanced the flavour. The authors concluded that the pure starter culture could be utilized to facilitate scaled-up pito production [164]. Lyumugabe et al [166] reported that hopping wort with V. amygdalina leaves resulted in the synthesis of polyfunctional thiols; however, it inhibited the production of 2-sulfanylethanol and 2-sulfanylethyl acetate.…”
Section: Volatile Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…delbrueckii and Sacch. cerevisiae (Djameh et al, 2019). However, this may not be a sustainable solution due to cost implications.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…Research to date has focused on optimizing the sorghum brewing process and obtaining a finished product with sensory characteristics that meet consumer acceptability [2]. The studies carried out focused on the possibility of using sorghum as an adjuvant to obtain beer, either in ground or extruded form in a proportion of 40-60% compared to barley malt [2,3,17,18] or used in beer manufacturing at 100% sorghum malt [13,[18][19][20]. The presence of sorghum beers on the market is recognition of the possibility of using this grain in brewing.…”
Section: Introductionmentioning
confidence: 99%